Coconut waste as a source for biodiesel production - Sulaiman, Sarina; Abdul Raman , Abdul Aziz; Mohamed Kheireddine Taeib, Aroua (2010)
Biodiesel industry needs a cheaper and economical viable raw material that can replace the currently used vegetable oil. Obtaining cheaper raw materials are one of the continuous targets of many biodiesel producing facilities since 70 to 95 % of the production costs are attributed to raw materials. One of the main options is to use waste material from animal and plant sources. In this study, coconut waste is used to produce biodiesel using methanol and KOB. The oil content in coconut waste varies from 10-11 wt%. The highest yield, 64 % is achieved with 5 wt% of KOB within 3 hr by mixing raw material and methanol.